Growth and results test of adaptive superior rice varieties through integrated components in the rainfed of Central Java. Issue 3 (July 2021) - Susila, A; Oelviani, R; Haryanto, W; Winarni, E; Jauhari, S
Abstract: The study aims to find new adaptive rice varieties with superior potential that was core out in three districts in 2016 growing season. The study area was 2, 000 m 2 each involving farmer cooperators. The assessment method used was the on farm research participant (OFCOR) approach in the demonstrations plot area. The superior varieties tested were Inpari 30, Inpari 10, Mekongga, and Ciherang variety as comparison. The parameters observed included the variability of plant growth and yields component, pest attack, and farmers response. The analytical method used was ANOVA to compare the mean of each tested variable using the Least Significance Difference (LSD) advanced test. The results show that the diversity of the new superior variety of Inpari 30 by applying the integrated components provided the highest growth performance and yield compared to the Ciherang variety, that is commonly planted by farmers, with an increase of 1.9 t/ha (36.5%) GKG and the Mekongga 1.7 t/ha (32%) GKG. The lowest yields were obtained for the Inpari to variety of 5.1 t/ha GKG and Ciherang. Mekongga and Inpari 30 had the same chance to be adapted more quickly by farmers because it provides increased yields and has the potential to be developed as site specific land.